A comparison of the antibacterial activity of some African black soaps and medicated soaps commonly used for the treatment of bacteria-infected wound - Olufunmiso O. Olajuyigbe; Morenike O. Adeoye-Isijola; Otunola Adedayo (AOSIS, 2017)
Background: Black soap is a medicinal product that could be harnessed for economic purpose if properly packaged, and misconception about its traditional use by herbalists is thrown overboard. Aims: To promote the relevance of these soaps for economic development, this study compared the antibacterial activity of black soaps with medicated soaps widely used against bacterial infections. Methods: The antibacterial activities of these soap samples were determined by agar diffusion and macrobroth dilution methods. Results: In this study, the statistical analysis of the inhibition zones showed that black soaps were significantly (p < 0.05) more active than medicated soaps used against the test bacterial isolates. The black soaps inhibited and killed the isolates better than the medicated soaps at the different concentrations used. The minimum inhibitory concentration for Klebsiella pneumoniae and Enterococcus faecalis ranged between 0.125 mg/mL and 2 mg/mL, Staphylococcus aureus (0.25-4) mg/mL, Escherichia coli (0.125-4) mg/mL and Pseudomonas aeruginosa (1-4) mg/mL. The result showed that K. pneumoniae and E. faecalis were the most susceptible, followed by E. faecalis > E. coli > S. aureus > P. aeruginosa. Conclusion: As a valuable medicinal output derivable from organic waste product that could be converted to wealth, African black soap production, utilisation and commercialisation have tremendous economic potentials. These soaps showed significant antibacterial activity greater than those of the medicated soaps. Hence, their use could be a better option in place of commercially available medicated and antiseptic soaps because of the degree of antibacterial activities they exhibited.